Analisis Uji Chemical Oxygen Demand (COD) pada Air Limbah Sawit di Dinas Lingkungan Hidup dan Kehutanan Provinsi Bangka Belitung - Rusdianto Rusdianto; Susanti Susanti; Tri Kusmita; Liyana Aryanto; Talitha Talitha; Mursid Mursid (Jurusan Fisika, Universitas Bangka Belitung, 2023)
Indonesia is the largest natural resource producing country in the world, the management of these natural resources requires assistance from various industries. In addition to providing an increase in the regional economy, industry can also cause an increase in waste which can cause environmental damage. Waste that is directly discharged into a water will cause a decrease in water quality, especially for palm oil liquid waste that has not met the specified wastewater quality standards. Chemical Oxygen Demand (COD) is one of the most important parameters in measuring water quality or water contamination load derived from dissolved oxygen in water or waste. Therefore, on this occasion, COD testing will be carried out to determine the level of dissolved oxygen in palm oil liquid waste. From the implementation of the calibration curve of COD testing in wastewater, it was declared accepted because the value of the test correlation coefficient was greater, namely r = 0.9994 than the value of the correlation coefficient set by SNI, namely r = 0.995. While precision data can be accepted if the value of % RPD is not greater than 10% of the test results.